Plotagon Story Media to Improve Learning Interest and Arabic Vocabulary Mastery: An Experimental Study - Dea Adelpina; Maman Abdurahman; Shofa Musthofa Khalid; Muhammad Irfan Wijaya (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Arabic language learning still faces challenges, particularly students' low learning interest and limited vocabulary mastery due to the dominance of conventional and less interactive teaching methods. Previous studies have examined the use of digital learning media; however, many of them focused on either learning interest or vocabulary mastery separately. This study aims to examine the effectiveness of Plotagon Story media in simultaneously improving students' learning interest and Arabic vocabulary mastery. The study employed a true experimental design with a pretest–posttest control group. The participants were 36 students assigned to the experimental and control groups. Data were collected using a learning interest questionnaire and an Arabic vocabulary mastery test, and analyzed using ANCOVA. The findings showed that students taught using Plotagon Story demonstrated higher learning interest and better vocabulary mastery than students receiving conventional instruction. These results indicate that animation-based digital media can promote more interactive and meaningful Arabic learning. This study suggests that Plotagon Story can serve as an alternative instructional medium to strengthen Arabic language instruction, particularly in madrasah contexts.